Analysis of the Influence of Service Quality, Ease of Access, and Trust on Users of the Single Submission Online Application (OSS) through the Satisfaction of Malinau Regency Business Actors - Abdul Muis; Erick Karunia; Syahran Syahran; Muh. Irfandy Azis; Deni Marsha (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study aims to analyze the influence of service quality, ease of access, and trust on the use of the Online Single Submission (OSS) application, and to examine its implications for the satisfaction of business actors in Malinau Regency. The study uses a quantitative approach with an explanatory survey design. The research sample comprised 280 business actors using OSS, selected through purposive sampling from a total population of 933. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The variables tested included service quality, ease of access, trust, use of OSS, and business actors' satisfaction. The results showed that ease of access and quality of service had a positive and significant effect on the use of OSS, while trust had no significant effect. Furthermore, the use of OSS has a positive and significant effect on the satisfaction of business actors. These findings imply that improving system usability and service quality is a priority for strengthening the policy on digital licensing services in border areas. The next study is suggested to include digital literacy and the quality of technological infrastructure as moderating factors.